Monte carlo study of a flattening filter-free 6 MV photon beam using the beamnrc code - Kajaria A.; Sharma N.; Sharma S.; Pradhan S.; Mandal A.; Lalit Aggarwal M. (My University, 2025)
Flattening Filter Free (FFF) photon beams have different dosimetric properties from those of flattened beams. The aim of this study is to evaluate the basic dosimetric properties of a flattening filter free 6 MV photon beam. A Monte Carlo simulation model was developed for a 6 MV photon beam based on Varian Clinic 600 unique performance linac operated with/without a flattening filter and dosimetric features including central axis absorbed dose, beam profiles and photon and electron spectra were calculated for flattened and unflattened cases separately. Absolute depth dose calculations showed an increase in dose rate with a factor of more than 2.4 for the unflattened 6 MV photon beam which is dependent on the depth. Percentage Depth Doses (PDDs) values were found to be lower for unflattened beam for all field sizes. The total Scatter Correction Factor (SCP) were found to have less variation with field sizes for unflattened beam indicating that removing of the filter from the beam line can reduce significant amount of head scatter. However surface doses were found to be higher for the unflattened beam due to more contamination electrons and low energy photons in the beam. Our study showed that increase in the dose rate and lower out-of-field dose could be considered as practical advantages for unflattened 6 MV photon beams. © 2017, Scientific Publishers of India. All rights reserved.